Methodologies of Stigma-Related Research Amongst Men Who Have Sex With Men (MSM) and Transgender People in Asia and the Pacific Low/Middle Income Countries (LMICs): A Scoping Review - Septarini, Ni Wayan; Hendriks, Jacqueline; Maycock, Bruce; Burns, Sharyn (Frontiers in Reproductive Health, 2021)
Much stigma-related research focuses on marginalized populations, including men who have sex with men (MSM) and transgender people. The importance of research in this area is widely recognized, however methodologies and measures vary between studies. This scoping review will collate existing information about how stigma-related research has been conducted in low/middle income countries (LMICs) within the Asia Pacific region, and will compare research designs, sampling frameworks, and measures. Strengths and limitations of these studies will inform recommendations for future stigma-related health research. A methodological framework for scoping studies was applied. Searches of Psych INFO, Scopus, ProQuest, Global Health and PubMed were used to identify articles. Stigma-related research amongst MSM and transgender communities, published between 2010 and 2019 in LMICs within the Asia Pacific region were included. A total of 129 articles based on 123 different studies were included. Of the 129 articles 51.19% (n = 66) were quantitative; 44.96% (n = 57) were qualitative and 3.88% (n = 5) were mixed methods studies. The majority of studies (n = 57; 86.36%) implemented a cross sectional survey. In-depth interviews (n = 20, 34.48%) were also common. Only 3.88% of studies utilized mixed-methods design. Non-probabilistic and probabilistic sampling methods were employed in 99.22 and 0.78% of studies respectively. The most common measures used in quantitative studies were the Center for Epidemiological Study on Depression (CES-D) (n = 18) and the Self Stigma Scale (SSS) (n = 6). Strengths and limitations proposed by researchers included in this review are summarized as lesson learnt and best practices in stigma-related research.